2016
DOI: 10.3390/f7120319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timber Harvest Intensities and Fertilizer Application on Stocks of Soil C, N, P, and S

Abstract: Abstract:The purpose of this study was to determine the stocks of available P and S, total N, and oxidizable C at depth in an Oxisol cultivated with Eucalyptus in Brazil following different timber harvest intensities and fertilizer application over 12 years. The harvest regimes considered were (i) conventional stem-only harvest (all forest residues were maintained on the soil); (ii) whole-tree harvest (only litter was maintained on the soil-all slash, stemwood, and bark were removed); and (iii) whole-tree harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
4
0
4
Order By: Relevance
“…These differences may be related to the shallow soil layers (0-40 cm) in our study, which limit the SOC related to root density [54]. Additionally, the litter quantity and turnover are very limited because more of the thinning residues, such as slashes, are left on-site without crushing, thus reducing the soil C stocks [55]. Determining SOC stock in large forest areas can be difficult because of the spatial variability in SOC stock and the different measurement errors associated.…”
Section: The C Stocks In Biomass and Soc For Different Pinus Spmentioning
confidence: 86%
“…These differences may be related to the shallow soil layers (0-40 cm) in our study, which limit the SOC related to root density [54]. Additionally, the litter quantity and turnover are very limited because more of the thinning residues, such as slashes, are left on-site without crushing, thus reducing the soil C stocks [55]. Determining SOC stock in large forest areas can be difficult because of the spatial variability in SOC stock and the different measurement errors associated.…”
Section: The C Stocks In Biomass and Soc For Different Pinus Spmentioning
confidence: 86%
“…Menegale et al [24], evaluating the effect of different types of wood harvesting and fertilizer application in a settlement of Eucalyptus grandis Hill Ex Maiden, reported that maintaining the forest harvesting residues in the soil contributes to the increasing C and N contents in the soil and is important for the supply of nutrients to the plants. Among the treatments evaluated by the authors, this process is more important in sandy soils, highly productive forests, and successive harvest cycles.…”
Section: Soil Chemical Analysismentioning
confidence: 99%
“…Duchesne and Houle [14] suggested that WTH of boreal forests in Quebec led to substantial net losses of potassium (K) and to a lesser extent calcium (Ca), but not magnesium (Mg). Menegale et al [15] observed a reduction…”
Section: Introductionmentioning
confidence: 93%